ANALISIS KELENGKAPAN SARANA ALAT DAN BAHAN PRAKTIKUM LABORATORIUM BIOLOGI BERBASIS KOMPETENSI DASAR KURIKULUM 2013 PADA MATA PELAJARAN BIOLOGI KELAS XI - Tia Nurul Safitri; Mariani Natalina. L; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aim to analyze the completeness of the tools and materialsfor the biology laboratory practicum based on the basic competencies of the 2013curriculum in class XI biology subjects. The type of this research is descriptivequantitative research. This research was conducted at SMA Negeri 8 Pekanbaru. Thetime of this research is in January-February 2022. The preparation of researchinstrument is carried out at the Study Program of Biology Education, Riau University.Data and data sources were obtained from biology laboratories, teachers andlaboratory assistants. The data collection instrument in the study were in the form ofobservation sheets and interview sheets. Based on the results of data analysis, it isknown that the biological laboratory equipment and materials at SMAN 8 Pekanbarubased on the Regulation of the Minister of National Education Number 24 of 2007obtained an average of 90.33 % with a very complete category. Meanwhile, thebiological laboratory equipment and materials at SMAN 8 Pekanbaru based on thebasic competencies of the curriculum 2013 obtained an average of 89.25 % with a verycomplete category. So it can be concluded that the tools and materials at SMAN 8Pekanbaru have met the standards that have been set, both in terms of indicators ofeducational equipment or teaching aids, experimental equipment, and consumables.Keywords: Analysis, Tools, Materials, Biology laboratories, Curriculum 2013